The Association between Postmenopausal Hormone Use and Risk of Type 2 Diabetes in Postmenopausal - Muhammad Hussain Afridi, Tahir Ghaffar, Itizaz Hayat, Mohammad Khalid Khan, Wiqas Ahmad (Pakistan Journal of Medical & Health Sciences, 2023)
Background: 100 postmenopausal women were examined for their usage of postmenopausal hormones and their risk of Type 2 diabetes. The findings demonstrated a significant association between the use of postmenopausal hormones and the incidence of Type 2 diabetes (odds ratio, 2.7; 95% confidence range, 1.4-5.1; P 0.001). Compared to women who did not take postmenopausal hormone treatment, those who did had a nearly 3-fold increased risk of diabetes. So, this research showed how crucial it is to consider postmenopausal hormones as a risk factor for Type 2 diabetes in postmenopausal women. Objectives: This study’s main goal was to determine postmenopausal hormone usage and the likelihood of developing Type 2 diabetes in 100 postmenopausal women at the Hayatabad Medical Complex in Peshawar, Pakistan; the specific goals were to define the features of the research population, evaluate the relationship between diabetes and postmenopausal hormone usage, and pinpoint risk factors for Type 2 diabetes in postmenopausal women. Methods: The research was carried out at the Hayatabad Medical Complex’s Department of Endocrinology in Peshawar, Between January 2022 And January 2023. The research’s participants included 100 postmenopausal women, aged 50 to 65, from the same institution who had been on postmenopausal hormone treatment for at least three months before the trial. Through blood tests (fasting glucose and hemoglobin A1c), participants’ risk of developing diabetes was evaluated. Additionally evaluated were other variables, including medical history, body mass index, and lifestyle choices that can influence the chance of getting Type 2 diabetes. Data were gathered using a semi-structured questionnaire, and descriptive statistics and logistic regression were used to analyze the results. Results: Postmenopausal hormone usage and risk of Type 2 diabetes were significantly correlated, according to the findings (odds ratio, 2.7; 95% confidence range, 1.4-5.1; P 0.001). Compared to women who did not take postmenopausal hormone treatment, those who did had a nearly threefold increased risk of diabetes. The research also found that obesity, a family history of diabetes, dining often away from home, and a lack of physical exercise were all substantially linked to an elevated risk of Type 2 diabetes in postmenopausal women (P 0.05). Conclusion: This research showed a significant relationship between Type 2 diabetes and postmenopausal hormone usage in postmenopausal women in Peshawar, Pakistan, aged 50 to 65. Compared to women who did not take postmenopausal hormones, those who did had a nearly three-fold increased risk of developing diabetes. In addition, the research found that other characteristics, including obesity, a family history of diabetes, dining out often, and a lack of physical exercise, were all substantially linked to a higher risk of Type 2 diabetes in postmenopausal women. Keywords: Postmenopausal Hormone Use, Type 2 Diabetes, Risk Factors, Obesity, Physical Activity, Postmenopausal Women